Serotyping Streptococcus pneumoniae by Multiplex PCR - Brito, D. A. (American Society for Microbiology, 2003)
The capsule is a major virulence factor of pneumococci, and it was shown that some capsular variants are associated with antimicrobial resistance and certain types of disease. Moreover, pneumococcal capsular typing has received renewed interest since the availability of conjugate vaccines, which include serotypes frequently associated with pediatric disease. Our aim was to develop a simple, reliable, and economical method for detecting epidemiologically important serotypes present in the proposed 11-valent conjugate vaccine. We designed primers based on the sequences available for the capsular types 1, 3, 4, 6B, 14, 18C, 19F, 19A, and 23F and combined them into seven multiplex PCRs. The method involves streamlined DNA template preparation and agarose gel electrophoresis to analyze the amplification products. A total of 446 pneumococci selected from among isolates colonizing the nasopharynx of children attending day care centers in Lisbon, Portugal, were typed both by conventional immunological techniques and by multiplex PCR. Capsular types identified by the PCR method invariably produced results concordant with the conventional serotyping technique. Even when the method presented does not fully type an isolate, the PCR data can guide the experimenter when using immunological serotyping. Multiplex PCR for the analysis of pneumococci provides an accurate, expeditious, and cost-effective way of reducing the number of strains that have to be serotyped by conventional immunological techniques.